Legal Nature of Fiduciary Duty in Civil Law of Ukraine - Urazova, Hanna (Teisė, 2022)
This article examines the legal nature of fiduciary duty in connection with the emergence of legal uncertainty and difficulties in law enforcement. The study begins with the definition of “fides”, “fiducia”, “legal duty” and “civil duty”, taking into account historical developments and case law. The characteristics of civil duty are given. The article ends with our own vision of the legal nature of fiduciary duty.